Design of nonlinear sliding mode controller for hydraulic fracturing of coalbed methane - YAO Shuncai; MA Tiehua; LI Feng (Gong-kuang zidonghua, 2016)
For coordination and synchronous control problem of multi motors of water pump for hydraulic fracturing in coalbed methane exploit process, a method of nonlinear sliding mode control was proposed, design method of nonlinear sliding mode controller for hydraulic fracturing of coalbed methane was given, and the controller performance was analyzed combining with hydraulic fracturing system of coalbed methane. The simulation analysis and experimental results show that concentration and single hole flow rate of coalbed methane were increased greatly in the process of coalbed methane fracturing exploit.